Phillis Wheatley and the Sentimental Tradition - Finch, Annie (Romanticism on the Net)

(untitled) (Université de Montréal, 2003)
AbstractThis essay describes critics’ relations to sentimentality, and then situates Phillis Wheatley’s poetry within it. Carefully distinguishing between Enlightenment poetry of sensibility and nineteenth-century sentimental poetry allows us to recognize Wheatley as among the first innovators of sentimentality, and it is precisely the politics of “race” which promotes such an innovation. Wheatley’s poetry presents us with a manifesto of sentimentality. She discovered the advantages, in the task of overcoming poetical oppression, of constructing a sentimental poetry that is genuinely intersubjective rather than subjective. What this examination of Wheatley’s work shows us is that the Romantic, expressivist aesthetic, allegedly so spontaneous, can be seen as in fact much more manipulative – at least politically – than Wheatley’s innovative, sentimentalist form.